2019
DOI: 10.1097/jcp.0000000000001053
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine Poisoning and Factors Influencing Severity

Abstract: Purpose/Background Quetiapine is a relatively new atypical antipsychotic with fewer adverse effects. It is increasingly prescribed to patients. The purpose of this study was to describe the cases of poisoning observed at the western France Poison Control Centre and identify potential risk factors that increase the severity of the cases. Methods This was a retrospective study of self-poisoning with quetiapine as reported by the western France Poison Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Otherwise, the sedation is considered an adverse effect. Several case reports and clinical trials have confirmed a considerable sedative effect in quetiapine overdose compared to most other antipsychotic drugs, 14 and an additive effect is observed when quetiapine is combined with other sedatives including alcohol and benzodiazepines 7,15,16 …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Otherwise, the sedation is considered an adverse effect. Several case reports and clinical trials have confirmed a considerable sedative effect in quetiapine overdose compared to most other antipsychotic drugs, 14 and an additive effect is observed when quetiapine is combined with other sedatives including alcohol and benzodiazepines 7,15,16 …”
Section: Introductionmentioning
confidence: 97%
“…Several case reports and clinical trials have confirmed a considerable sedative effect in quetiapine overdose compared to most other antipsychotic drugs, 14 and an additive effect is observed when quetiapine is combined with other sedatives including alcohol and benzodiazepines. 7,15,16 Respiratory depression has been described in 5% of patients admitted to hospital with overdose of quetiapine. 17 Furthermore, a register-based cross-over study of patients with chronic obstructive pulmonary disease (COPD) demonstrated a significant dose-dependent risk of acute respiratory depression associated with antipsychotics, including quetiapine.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic agents are associated with prolongation of the corrected QT interval (QTc), which might result in arrhythmia or syncope in cases of patient overdose [39,40]. Furthermore, it is known that among the most common symptoms when it comes to higher quetiapine doses or poisoning are the cardiovascular ones, namely tachycardia and hypotension [41]. This is in accordance with the staggered way in which quetiapine doses are prescribed.…”
Section: Discussionmentioning
confidence: 97%
“…36 Rising prescription rates have been strongly correlated with an increase in the rates of quetiapine-associated poisoning and mortality. [37][38][39] Given that no specific therapy reverses quetiapine toxicity, 40 this accentuates a need for caution in prescribing, especially off-label, with an overall objective of harm minimisation.…”
Section: Discussionmentioning
confidence: 99%